Subtitusi Tepung Ampas Tahu pada Pembuatan Brownies Kering Kulit Pisang - Inayah, Astrina Nur; Zahilah, Riska Nur; Ramadhan, Tri (Gorontalo Agriculture Technology Journal, 2025)
Tofu dregs are a by-product of soybean pulp which is pressed to extract its juice in making tofu. Tofu dregs have low economic value, are easily damaged and cannot be stored for long. However, wet tofu dregs are easily damaged and spoiled, so they need further handling to increase the shelf life of the tofu dregs and to be more flexible in use, for example by making flour. This research aims to analyze the effect of adding tofu dregs flour and kepok banana peel on the physical and organoleptic quality of dry brownies. Tofu dregs flour was used as a substitute for wheat flour with three variations in concentration (20%, 25%, 30%). Tests included color, aroma, taste and texture parameters through organoleptic tests using the hedonic scale method by 25 panelists. The results showed that the highest value of the color organoleptic test was in the BK2 treatment (4.36) with 25% tofu dregs substitution, the highest value of the aroma organoleptic test was in the BK3 treatment (4.21) with 30% tofu dregs substitution, the highest value of the taste organoleptic test was in treatment BK2 (4.29) with 25% tofu dregs substitution, and the highest value of the texture organoleptic test was in treatment BK0 (4.09) with 0% tofu dregs substitution. The use of tofu dregs flour gives an attractive deep brown color to the final product. This research concluded that the addition of tofu dregs flour and kepok banana peels could increase the panelists' appeal to dry brownies.